A TECHNIQUE OF PAINTING. MY COLLAGE ART: चित्रकला की एक तकनीक . मेरी कोलाज कला - Mahobe, Yatindra (International Journal of Research -GRANTHAALAYAH, 2019)
Kala is not just a necessity for attaining pleasure, but the inclusion of public welfare as well as inspiration and inspirational life is also unacceptable. Forty percent of the artists in India are those whose artworks are engaged in art and life, where there is nothing like a horizontal ring here. There is nothing other than a ring. Today, there are some artists who consider art to be a means of attaining only a partial enjoyment. They are able to create an art form that is self-sufficiently happy, by referencing the basic features of painting. Therefore, this type of art is organized without disturbing the public and society. I think that there must be something like this in the artist that the expression of the artist should reach the public. कला चसर्फ आनिंद प्राप्ति का जररया नहीिं है एबप्ति उसमें जनकल्याण यथाथफता एििं प्रेरणादायक भािना का समािेश भी अचनिायफ है। भारत में पिास प्रचतशत कलाकार ऐसे हैं चजनकी कलाकृचतयॉिं कला दीर्ाफओिं में लगी रहती हैं चजनमें आड़ी.चतरछी रेखायें यहॉिं.िहााँ र्ैले रिंग के अलािा कुछ भी नहीिं होता। आज कुछ कलाकार ऐसे भी है जो कला को चसर्फ आप्तिक आिंनद की प्राप्ति का साधन मानते हैं।ये चित्रकला के आधारभूत चनयमो का उल्लिंर्न कर ऐसी कलाकृचत तैयार करते है जो चसर्फ स्वान्तः सुखाय है। अतः इस प्रकार की कला जनसामान्म एििं समाज की परिाह चकये बगैर चनचमफत होती है।मुझे लगता है चक कलाकार में ऐसा या इतना कुछ जरूर होना िाचहए चक कलाकार की अचभव्यप्ति जनसामान्म तक पहाँि जाये।